Sophia Korvin (Sophia Kovalevsky) (1850-1891) a heroine of mathematics: Sofía Korvin (Sofía Kovalevsky) (1850-1891) una heroína de las matemáticas - Arguedas T, Vernor (2020)
Some aspects of the life of Sofía Korvin (Sofía Kovalevsky) in her facets as a writer, mathematician, social activist and tireless fighter for women’s rights are analyzed.